Early cessation of exclusive breastfeeding and associated factors in Ethiopia: a systematic review and meta-analysis - Tadele Emagneneh; Chalie Mulugeta; Abebaw Alamrew; Betelhem Ejigu; Wagaw Abebe (Frontiers in Nutrition)
BackgroundEarly cessation of exclusive breastfeeding poses significant risks to infant health by depriving them of essential immune-boosting and nutritional benefits found in breast milk. The First 1,000 Days, from conception to a child’s second birthday, is a critical window for growth and development. EBF during this period plays a vital role in ensuring optimal nutrition, strengthening immunity, and reducing childhood morbidity and mortality. However, early discontinuation of EBF remains a major public health concern in Ethiopia, contributing to malnutrition and increased susceptibility to infections.AimDespite global efforts to promote exclusive breastfeeding, early cessation remains a growing concern. This systematic review and meta-analysis assess the prevalence and associated factors of early cessation of EBF to provide evidence-based insights for improving breastfeeding practices.MethodsWe conducted a comprehensive search of published papers in Scopus, PubMed, Google Scholar, and Web of Science databases, up to March 1, 2024, without any restrictions on publication date. Records were screened, data extracted, and the risk of bias was independently assessed by five reviewers. Study heterogeneity was evaluated using Cochrane I2 statistics, while publication bias was assessed through the Egger-Begg test and funnel plots. A random-effects model was used to estimate the pooled prevalence of early cessation of EBF.ResultsThe analysis included 3,726 participants from 9 studies: five cross-sectional, two case–control, and two cohort studies. The overall pooled prevalence of early cessation of EBF was 43.31% (95% CI: 27.30–59.32). Several factors were significantly associated with early cessation, including urban residence (OR = 2.01, 95% CI: 1.7–2.30), lack of maternal education (OR = 2.79, 95% CI: 1.86–3.72), maternal employment (OR = 2.88, 95% CI: 1.36–4.41), poor knowledge of breastfeeding (OR = 2.08, 95% CI: 1.45–2.70), delayed initiation of breastfeeding (OR = 2.88, 95% CI: 1.57–2.18), and being a first-time mother (OR = 2.08, 95% CI: 1.45–2.70).ConclusionThe pooled prevalence of early cessation of EBF in Ethiopia was found to be 43.31% (95% CI: 27.30–59.32), indicating that nearly half of Ethiopian infants are not breastfed exclusively for the recommended 6 months. Factors significantly associated with early cessation include urban residence, non-educated mom, employment, poor maternal knowledge, delayed breastfeeding initiation, and Primipara (being a first-time mother). These findings underscore the need for targeted interventions, such as community-based education programs, workplace breastfeeding support policies, and strategies to promote early breastfeeding initiation and improve maternal knowledge. Addressing these factors could help reduce early cessation, increase sustained EBF rates, and improve child health outcomes.